2013
DOI: 10.1007/s12282-013-0497-8
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node ratio and breast cancer prognosis: a meta-analysis

Abstract: Due to the heterogeneity of lymph node examination and the conflicting results existing for the same classification of lymph node ratio (LNR), it is necessary to conduct a meta-analysis to evaluate the prognostic effects of different LNRs on breast cancer. PubMed, EMBASE, and ISI Web of Knowledge were searched to find all published cohort studies that evaluated the prognostic value of different LNRs on breast cancer. The outcomes were overall survival (OS), disease-free survival (DFS), breast cause-special sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(34 citation statements)
references
References 31 publications
0
32
0
2
Order By: Relevance
“…Now, the recent metaanalysis of Li et al [103] covering more than 3,400 patients as well as further retrospec tive cohort analyses confirmed statistically significant benefi cial effects of PMRT even in patients with 1-3 positive lymph nodes in terms of locoregional tumor control. Therefore, PMRT should be recommended for patients with 1-3 positive lymph nodes (LoE 1a, A, AGO +) [102][103][104]106]. At present, it is unclear which subgroups with indication for PMRT (high risk, pN0 or inter mediate pN1 (1-3 lymph nodes)) would benefit from an inclusion of the regional lymph nodes into the radiotherapy target.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…Now, the recent metaanalysis of Li et al [103] covering more than 3,400 patients as well as further retrospec tive cohort analyses confirmed statistically significant benefi cial effects of PMRT even in patients with 1-3 positive lymph nodes in terms of locoregional tumor control. Therefore, PMRT should be recommended for patients with 1-3 positive lymph nodes (LoE 1a, A, AGO +) [102][103][104]106]. At present, it is unclear which subgroups with indication for PMRT (high risk, pN0 or inter mediate pN1 (1-3 lymph nodes)) would benefit from an inclusion of the regional lymph nodes into the radiotherapy target.…”
Section: Neoadjuvant Chemotherapymentioning
confidence: 99%
“…Lymph node ratio has been reported to be associated with prognosis in a variety of cancers, including oesophageal, gastric, colonic and breast. [6][7][8][9] In 2004, Berger et al examined the association of lymph node ratio and total nodes examined on survival in patients with PDAC and reported that only lymph node ratio had an impact on overall and disease-free survival. 10 Further studies were subsequently conducted on the prognostic role of lymph node ratio, lymph node ratio to delineate the most predictive marker of survival, but there was no consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Metastasis remains a key risk factor for lowering the overall survival rate in breast cancer, with the regional axillary lymph nodes becoming involved first during this process (22). A previous study demonstrated that, among patients with stage 0-II breast cancer, local recurrences were 2.8 times less frequent in radically treated patients, compared with conservatively treated patients, for whom lymph node recurrences were twice as common (23).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study demonstrated that, among patients with stage 0-II breast cancer, local recurrences were 2.8 times less frequent in radically treated patients, compared with conservatively treated patients, for whom lymph node recurrences were twice as common (23). Accurate and effective evaluation of the status of axillary lymph nodes is of prognostic significance in patients with breast cancer (22).…”
Section: Discussionmentioning
confidence: 99%